Genomic and molecular alterations in human inflammatory bowel disease-associated colorectal cancer. Issue 6 (July 2020) - Muller, Marie; Hansmannel, Franck; Arnone, Djesia; Choukour, Myriam; Ndiaye, Ndeye Coumba; Kokten, Tunay; Houlgatte, Rémi; Peyrin-Biroulet, Laurent
Patients with inflammatory bowel disease are at increased risk of colorectal cancer, which has worse prognosis than sporadic colorectal cancer. Until recently, understanding of pathogenesis in inflammatory bowel disease-associated colorectal cancer was restricted to the demonstration of chromosomic/microsatellite instabilities and aneuploidy. The advance of high-throughput sequencing technologies has highlighted the complexity of the pathobiology and revealed recurrently mutated genes involved in the RTK/RAS, PI3K, WNT, and TGFβ pathways, leading to potentially new targetable mutations. Moreover, alterations of mitochondrial DNA and the dysregulation of non-coding sequences have also been described, as well as several epigenetic modifications. Although recent studies have brought new insights into pathobiology and raised the prospect of innovative therapeutic approaches, the understanding of colorectal carcinogenesis in inflammatory bowel disease and how it differs from sporadic colorectal cancer remains not fully elucidated. Further studies are required to better understand the pathogenesis and molecular alterations leading to human inflammatory bowel disease-associated colorectal cancer.